2000
DOI: 10.1111/j.1601-0825.2000.tb00317.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral tuberculosis: a clinical evaluation of 42 cases

Abstract: OBJECTIVES: A retrospective review of a large series of oro‐facial cases of tuberculosis to analyse clinical, histo‐pathological, and radiological aspects, as well as those of chemotherapy. MATERIALS AND METHODS: A total of 42 cases of tuberculosis of the oro‐facial region were examined. Thirteen patients had a primary form and 29 a secondary form of the disease. Diagnosis was based on careful clinical examination, Mantoux reaction, histopathological examination, microbiological cultures and immunological inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 19 publications
4
96
1
3
Order By: Relevance
“…Clinical cases of tuberculosis in children (Mignogna et al 2000;Ito et al 2005;Ebenezer et al 2006), have not shown any type of enamel hypoplasia nor the dental abnormalities resembling those described in the cases above. In skeletal cases of possible tuberculosis, dental abnormalities including linear enamel hypoplasia (Matos et al 2011;Bedić et al 2015), bands of decreased enamel thickness and carious lesions have been observed (Formicola et al 1987).…”
Section: Differential Diagnosismentioning
confidence: 89%
“…Clinical cases of tuberculosis in children (Mignogna et al 2000;Ito et al 2005;Ebenezer et al 2006), have not shown any type of enamel hypoplasia nor the dental abnormalities resembling those described in the cases above. In skeletal cases of possible tuberculosis, dental abnormalities including linear enamel hypoplasia (Matos et al 2011;Bedić et al 2015), bands of decreased enamel thickness and carious lesions have been observed (Formicola et al 1987).…”
Section: Differential Diagnosismentioning
confidence: 89%
“…Les lésions buccales de la tuberculose peuvent être primitives (20 % des cas) ou secondaires à une localisation pulmonaire (80 % des cas) [14]. Le mécanisme de la tuberculose primitive est incertain : le bacille serait directement inoculé dans la muqueuse buccale [15]. La tuberculose secondaire affecte plus fréquemment les personnes âgées.…”
Section: Discussionunclassified
“…T uberculosis (TB) of the superficial lymph nodes is the most common form of extra pulmonary tuberculosis in children, and it is the most common complication of a correlation between lymph node tuberculosis and the location, distribution and amount of the infected glands. [10][11][12] Enlargement of the lymph nodes outside the cervical area indicates a serious form of TB with systemic process. 7,13 Another opinion stated that multiple process is frequently found in the enlargement of superficial lymph nodes caused by MTB.…”
Section: Resultsmentioning
confidence: 99%